2009
DOI: 10.1021/cg801416a
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Metastable Polymorphs of Phenobarbital by Isomorphic Seeding

Abstract: Six metastable polymorphs (V, VII-XI) of phenobarbital (Pbtl) were produced by melt crystallization via seeding with corresponding isomorphic barbiturate homologues, following the teachings of earlier thermoanalytical studies of isopolymorphic relationships and utilizing the melting phase diagrams of Pbtl admixtures with various 5,5-substituted barbituric acid derivatives. The Pbtl forms and their solid solutions were analyzed with hot-stage microscopy, powder X-ray diffraction, and infrared spectroscopy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 61 publications
5
69
0
Order By: Relevance
“…However, these methods are difficult to control in terms of avoiding the formation of more than one polymorph [45,46]. Moreover, the isolation of a metastable polymorph is difficult and challenging before it undergoes a solvent-mediated phase transformation to the more stable form.…”
Section: Stabilization Of Non-stable Phasesmentioning
confidence: 99%
“…However, these methods are difficult to control in terms of avoiding the formation of more than one polymorph [45,46]. Moreover, the isolation of a metastable polymorph is difficult and challenging before it undergoes a solvent-mediated phase transformation to the more stable form.…”
Section: Stabilization Of Non-stable Phasesmentioning
confidence: 99%
“…25 It was concluded that for systems in which isomorphic structural relationships are known to exist, appropriately chosen additives can be used to stabilize unstable crystal forms that are unable to be isolated during conventional solvent or melt crystallization experiments. N-(1-naphthyl)-succinimide was used as a model case to test the relative merits of a "quenched nucleation" protocol and conventional homogeneous nucleation procedures, with different polymorphic outcomes being observed depending on the procedure followed.…”
Section: Studies Of Preparative and Isolation Methodologymentioning
confidence: 99%
“…Zencirciet al investigated the crystallization of the phenobarbital using a variety of structurally related compounds as heterosurface (Zencirci et al, ). They were able to identify six metastable polymorphs of Phenobarbital (Form V and VII to XI) which were not reported previously by either solution crystallization or melt crystallization.…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%
“…Only two polymorphic forms of the sulfamethoxazone were known till Price et al recently discovered two more polymorphs III and IV using diverse polymer library as heterosurface (Price et al, ). Phenobarbital was discovered in 1912 and exists in 11 polymorphic forms, wherein, six novel polymorphs were discovered recently using isomorphous heterosurfaces (Zencirci et al, ). Fenofibrate is one of the blockbuster antihyperlipidemic agents identified with two novel polymorphs when crystallization was attempted with pharmaceutically relevant excipients like talc (Tipduangta et al, ) and HPMC (Shi et al, ) as heterosurfaces.…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%